Towards Digitalization of Performance Management as a Strategy for Improving Sustainable Education - Arwen, Desri; Sono, Mohammad Gifari (West Science Information System and Technology, 2025)
This study explores the digitalization of performance management as a strategy to enhance sustainable education in Indonesia. Using a qualitative approach, data were gathered through in-depth interviews with five key informants, including policymakers, school administrators, educators, technology experts, and educational researchers. The findings reveal that digitalized systems offer benefits such as real-time monitoring, data transparency, and improved collaboration among educators. However, challenges persist, including infrastructural limitations, digital literacy gaps, and resistance to change. Strategies such as capacity building, pilot projects, and inclusive planning are recommended to address these barriers. The study underscores the potential of digital performance management to transform education sustainably, provided these challenges are systematically mitigated.